The Rise of India in Sports: A Mirror to National Pride and Identity - Sumanth S. Hiremath (RIRAI Publisher, 2026)
This article examines the intricate relationships that exist between Indian national identity and sport, emphasising how widespread participation and sporting accomplishments promote patriotism and a sense of shared national identity. Using a mixed-methods research design and based on Benedict Anderson's theory of